2018
DOI: 10.1002/jts.22273
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Aggregated and Specific Combat Exposures: Associations Between Combat Exposure Measures and Posttraumatic Stress Disorder, Depression, and Alcohol‐Related Problems

Abstract: Research has shown combat exposure to be associated with negative mental health outcomes. Different combat exposure measures are not composed of the same combat experiences, and few combat exposure measures have been directly compared to another measure. Furthermore, research about the unique associations between specific combat experiences and mental health is lacking. We investigated associations between new-onset posttraumatic stress disorder (PTSD), new-onset depression, and alcohol-related problems and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 41 publications
7
44
0
1
Order By: Relevance
“…While the DSM-IV was used because data collection pre-dated the publication of the DSM-5th edition (DSM-V), future studies should replicate these findings using DSM-V criteria. Combat was assessed from a measure with only 5 items; however, a recent study found that this combat measure performed similarly to a more detailed measure [37]. While the relatively short average length of follow-up reduced statistical power for examining potential effect modification and estimating relative risks specific to the rarer autoimmune diseases of interest, this limitation could be mitigated in future research incorporating extended follow-up of this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…While the DSM-IV was used because data collection pre-dated the publication of the DSM-5th edition (DSM-V), future studies should replicate these findings using DSM-V criteria. Combat was assessed from a measure with only 5 items; however, a recent study found that this combat measure performed similarly to a more detailed measure [37]. While the relatively short average length of follow-up reduced statistical power for examining potential effect modification and estimating relative risks specific to the rarer autoimmune diseases of interest, this limitation could be mitigated in future research incorporating extended follow-up of this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Deployment dates were provided by DMDC, and self-report of combat exposures was assessed at each follow-up based on at least 1 affirmative response to witnessing any of the following: a person's death due to war, disaster, or tragic event; instances of physical abuse; dead or decomposing bodies; maimed soldiers or civilians; or prisoners of war or refugees ( Porter et al, 2018 ). At each subsequent follow-up survey, participants were asked whether these experiences had occurred in “the last 3 years”; thus, reports of experiences could be linked with deployments occurring during the same 3-year interval.…”
Section: Methodsmentioning
confidence: 99%
“…However, only 19% of these patients seek medical help for themselves, where most of them were alcohol dependence [ 4 ]. Despite the availability of information on the correlation between depression and SUD and/or alcohol dependence, their causality is still controversial [ 5 ]. The association between substance use and depression has been specified more significantly for some substances, including alcohol, cannabis, and opioids.…”
Section: Introductionmentioning
confidence: 99%